2021
DOI: 10.1177/0885328221991948
|View full text |Cite
|
Sign up to set email alerts
|

PEG-α-CD/AM/liposome @amoxicillin double network hydrogel wound dressing—Multiple barriers for long-term drug release

Abstract: Wound infection and poor wound healing are the major challenges of wound treatment. Antibiotic drug treatment is the effective way to inhibit wound infection. It is necessary to achieve sustained release of antibiotics to get a longer treatment for wound infection. The double network hydrogels based on liposome, polyethylene glycol (PEG), α- cyclodextrin ( α-CD) and acrylamide (AM) were developed, in which liposome acts as amoxicillin repository. Because the drug would release from the multiple barriers includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The material is considered to have good biocompatibility when the cytotoxicity is less than 30%. [ 32 ] Cytotoxicity test was performed to evaluate the cytocompatibility of the hydrogels. As shown in Figure a), the cell viability of higher than 95% indicated that the hydrogels had good cytocompatibility, which met the evaluation criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The material is considered to have good biocompatibility when the cytotoxicity is less than 30%. [ 32 ] Cytotoxicity test was performed to evaluate the cytocompatibility of the hydrogels. As shown in Figure a), the cell viability of higher than 95% indicated that the hydrogels had good cytocompatibility, which met the evaluation criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels' capacity to efficiently absorb exudate plays a vital role in managing chronic, bacterial infected wounds [52,53]. As a desired side effect, hydrated wound dressings help to control the temperature of the wound-affected area, accelerating the healing process [54][55][56][57][58][59].…”
Section: Challenges Related To Hydrogel-based Wound Dressingsmentioning
confidence: 99%
“…Wound dressings, as a controlled release drug delivery system, loading drugs or epidermal growth factors and achieving their fixed-point and continuous release have been attributed to crucial roles in wound healing [68,70]. We selected horseradish peroxidase (HRP) as a model drug to examine the drug release kinetics of SPD and monitored the drug release profile of HRP from the SPD for 22 d. As shown in figure 2(F), the release behavior of HRP from the SPD apparently displayed a bi-phasic process: a fast release stage within 14 d, followed by a plateau stage.…”
Section: The Sustained Drug Release From Spdmentioning
confidence: 99%